Study on the attenuation relationship of the acceleration envelope parameters for the Wenchuan earthquake aftershocks - Yin, Deyu (Frontiers in Earth Science, 2024)
The seismic attenuation relationship between ground motion parameters (such as peak acceleration and response spectra value) and seismic parameters (such as magnitude and epicentral distance) is an important foundation for seismic hazard analysis and the core of determining seismic input parameters for seismic resistance engineering. The acceleration envelope parameters, which describe the relationship between ground motion intensity and time variation, are primarily used for artificially synthesizing seismic motion. At present, little research has been performed on the attenuation relationship of acceleration envelope parameters in the Longmenshan fault zone on the eastern side of the Tibetan Plateau in China. Therefore, this study selected the Mw4-6 aftershock records of the 2008 Wenchuan earthquake that occurred on the Longmenshan fault zone and established a commonly used three segment envelope model parameter attenuation relationship. We classified aftershock records based on their source mechanisms and obtained attenuation relationship models for thrust slip aftershocks, thrust and strike slip aftershocks, and strike slip aftershocks. The results are as follows: (1) The thrust slip aftershock records had the longest rising stage which is the time difference from the arrival of P-waves to the beginning of the stable sustained stage of seismic motion. Thrust and strike slip aftershocks records had the longest stable sustained stage period and the slowest attenuation at the tail of the record. (2) The attenuation relationship of the acceleration envelope parameters commonly used in Chinese engineering for artificially synthesizing seismic motion is based on the strong earthquake records in the western United States. But, compared to the attenuation characteristics of the acceleration envelope function in the western United States, the Mw4-6 earthquake records on the Longmenshan fault zone had a slower attenuation rate at the tail of the record. So, accurately artificially synthesizing seismic motion through envelope parameter attenuation model requires the use of attenuation model established by earthquake records in this region.